The development of communication research in Indonesia in 2001-2020 - Justito Adiprasetio (Universitas Padjadjaran, 2022)
No systematic review and/or meta-analysis has attempted to map the macro and comprehensive landscape conditions, developments, and trends of communication research in Indonesia in the past few decades. Therefore, it is challenging to measure the progress that Indonesian communication scholars have achieved. This study analyzed 3108 articles distributed in reputable communication scientific publications in Indonesia, spanning two decades: January 2001 to March 2020. This study found many optimistic or skeptical justifications of Indonesian communication scholars about the development of communication epistemology in Indonesia. During the two decades, although there had been an increase in publications relying on quantitative approaches, it can be seen that the dominance of qualitative approaches was irreplaceable. The trend of increasing research using a quantitative approach was only a conversion from literature review articles widely published in the early 2000s. The Ministry of Communication and Information, Indonesia, in the second position, as the institution that contributes to the most authors of scientific articles after the Universitas Islam Bandung in the first place, and even surpassing Universitas Hasanuddin, Universitas Padjadjaran dan Universitas Diponegoro showing that the agency of state institutions is one of the active actors in communication knowledge production and reproduction in Indonesia. The increasing number of citations over the past two decades indicates that Indonesian scholars are experiencing enrichment of reference sources and interconnection with other scholars. However, based on keyword trends, Indonesian research’s deliberative and progressive vision has yet to appear dominant.